Screening of Mango Rootstock For Saline Tolerance (SAARC Journal of Agriculture, 2021)
An experiment was conducted at Fruit Tree Improvement Project, Fruit Tree Improvement Programme, Bangladesh Agricultural University-Germplasm Center (FTIP, BAU-GPC), Bangladesh Agricultural University (BAU), Mymensingh during the period of April 2020 to June 2020 to study the performance of selected mango rootstocks for the saline area. The two-factor experiment consisted of four mango rootstock varieties such as V1 = BAU Aam-9, V2 = BAU Aam-6, V3 = BAU Aam-4 and V4 = Amropali and six salinity treatments namely control S1 = 0 dSm-1, S2 = 4 dSm-1, S3 = 8 dSm-1, S4 = 10 dSm-1, S5 = 12 dSm-1 and S6 = 14 dSm-1. The experiment was conducted following randomized complete block design with three replications. Results revealed that rootstock line and salinity levels had significant influences on various rootstock characters viz. length of rootstocks, number of leaves and percent rootstocks success and survivability. In case of varietal effect, the highest number of leaves (32.44) found in BAU Aam-6 and the lowest number of leaves was recorded in Amropali (22.55) at 90 days after transplanting. The longest rootstock length observed in 90 DAT which (54.83 cm) found in BAU Aam-9and shortest rootstock recorded in Amropali (47.94 cm). The highest survivability (51.44%) was recorded in BAU Aam-9 and the lowest survivability recorded in Amropali (33.88%). In case of salinity treatments, the highest survivability (95.83%) was recorded in control and the lowest survivability (0.00%) recorded in 14 dsm-1 at 90 DAT. Interaction of rootstock varieties and different salinity treatments showed significant variation on the length leave and survivability of rootstocks at 90 DAT. The maximum number of rootstock leaves recorded in V2S2 (46.33) and lowest number of leave recorded in V4S6 (7.66). The highest rootstock length was found in V1S3 (78.00 cm) and lowest in V1S2 (21.66 cm). The highest Survivability (100 %) observed in V1S1, V1S2, V2S1, V2S2 and V4S1. From the above mentioned it can be said BAU Aam - 9 and BAU Aam – 6 rootstock varieties performed best from 0-8 dSm-1 salinity. The overall salinity tolerance was graded as follows: BAU Aam - 9>BAU Aam – 6> BAU Aam-4>Amropali rootstock line.SAARC J. Agric., 19(1): 93-102 (2021)